2023
DOI: 10.1152/physrev.00025.2021
|View full text |Cite
|
Sign up to set email alerts
|

Chloride transporters controlling neuronal excitability

Abstract: Synaptic inhibition plays a crucial role in regulating neuronal excitability, which is the foundation of nervous system function. This inhibition is largely mediated by the neurotransmitters GABA and glycine that activate Cl--permeable ion channels, which means that the strength of inhibition depends on the Cl- gradient across the membrane. In neurons, the Cl- gradient is primarily determined by two secondarily-active cation-chloride cotransporters (CCCs), NKCC1 and KCC2. CCC-mediated regulation of the neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 372 publications
0
17
0
Order By: Relevance
“…More recently, it has been reported that remote neuronal activity or proximally synapse formed by glioma–neuron interactions can drive glioma progression. 14 , 26 , 37 Based on the role of chloride transporters that regulate inhibitory synaptic plasticity mediated by the neurotransmitter GABA, 38 we hypothesize that SLC12A5 maintains the function of GABA receptor through regulating Cl − gradient across the membrane in turn blocking neuronal excitability induced by glioma–neuron interactions. This may be the mechanism why overexpression of SLC12A5 in tumour cell suppress its proliferation and migration and low expression level of gene in high‐grade glioma, which need relatively extensive works to be validated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that remote neuronal activity or proximally synapse formed by glioma–neuron interactions can drive glioma progression. 14 , 26 , 37 Based on the role of chloride transporters that regulate inhibitory synaptic plasticity mediated by the neurotransmitter GABA, 38 we hypothesize that SLC12A5 maintains the function of GABA receptor through regulating Cl − gradient across the membrane in turn blocking neuronal excitability induced by glioma–neuron interactions. This may be the mechanism why overexpression of SLC12A5 in tumour cell suppress its proliferation and migration and low expression level of gene in high‐grade glioma, which need relatively extensive works to be validated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The CCC NKCC1 plays a crucial role in cellular osmolarity by regulating ionic balance and water flux, and it is currently targeted to treat a variety of related imbalance diseases, e.g. brain disorders including neurodevelopmental, neurodegenerative, neurological, disorders, hydrocephalus, as well as cancer. Motivated by the recent structural data on NKCC1 in different conformationsIO and OO stateswe built and simulated atomistic models of human NKCC1, where the transporter is embedded in the membrane. We used these models to run multiple μs-long MD equilibrium and enhanced sampling simulations of those key IO and OO states and capture the exact protein dynamics for IO ↔ OO transitions.…”
Section: Discussionmentioning
confidence: 99%
“…NKCC1 is also highly expressed on the apical membrane of the choroid plexus, where it plays a major role in producing and regulating cerebrospinal fluid (CSF). Importantly, in recent years, extensive research has shown that an increased intracellular Cl – concentration in neurons is symptomatically related to multiple neuropathologies and also glioblastoma, along with the growing body of literature, showing NKCC1’s important pathological role in increased CSF production. Accordingly, normalization of intracellular Cl – concentration and of CSF hypersecretion in the brain by modulation of CCC (including NKCC1) functions is considered a very promising strategy for neuroscience drug discovery. , A fundamental understanding of NKCC1’s structure, dynamics, and overall conformational motions for ion passage may therefore open new avenues for therapeutic interventions on many human disorders ranging from brain and hearing to kidney and cancer diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of ASD involves an imbalance between excitation and inhibition. In neurons, the Cl − importer NKCC1 (Na-K-Cl cotransporter 1) is counterbalanced by the Cl − extruder KCC2 (K-Cl cotransporter 2) [ 28 , 29 , 30 ]. NKCC1 and KCC2 serve as the primary regulators of the transmembrane Cl − gradient in neurons [ 31 ].…”
Section: Introductionmentioning
confidence: 99%